Emerging aqueous two-phase systems: from fundamentals of interfaces to biomedical applications. (21st November 2019) - Chao, Youchuang; Shum, Ho Cheung
Abstract : This review summarizes recent advances of aqueous two-phase systems (ATPSs), particularly their interfaces, with a focus on biomedical applications. Abstract : Aqueous two-phase systems (ATPSs) have been recognized for their applications in extraction, separation, purification, and enrichment of (bio)molecules and cells. Recently, their unique ability to create aqueous–aqueous interfaces through phase separation and the characteristics of these interfaces have created new opportunities in biomedical applications. In this review, we summarize recent progress in understanding the dynamics at aqueous–aqueous interfaces, and in developing interface-assisted design of artificial cells and cyto-mimetic materials, fabrication of cyto- and bio-compatible microparticles, cell micropatterning, 3D bioprinting, and microfluidic separation of cells and biomolecules. We also discuss the challenges and perspectives to leverage the unique characteristics of ATPSs and their interfaces in broader applications.